Supported Playgroup Participation During Infancy and Developmental Health at School Entry: The Healthy Baby Community Support Program in Manitoba, Canada - Struck, Shannon; Afifi, Tracie; Nickel, Nathan; Theule, Jennifer; Brownell, Marni (International Journal of Population Data Science, 2020)
Introduction Roughly 30% of children in Manitoba are vulnerable in one or more important areas of development at school entry. The Healthy Baby Community Support Program (HBCSP) is a universally accessible supported playgroup that operates across Manitoba to support mothers and babies up to 1 year postpartum. Objectives and Approach This study used HBCSP attendance records linked to whole-population health, education, and social services data to measure the relationship between maternal HBCSP participation and later developmental health of children at school entry. Mother-infant dyads who lived in areas with access to weekly programs and had a valid Early Development Instument record (n=14,995) where included. Logistic regression models controlled for child characteristics and inverse probability treatment weights (IPTW) were applied to balance the exposed and unexposed groups for measured maternal characteristics. Results HBCSP participants had significantly higher odds of having an at-risk profile (e.g., use of alcohol/drugs in pregnancy, low income, single mother) compared with non-participants. Adjusted outcome models showed increased odds of vulnerability in multiple domains of development. However, after applying IPTW from multi-sector data, HBCSP participation was associated with decreased odds of developmental vulnerability in 3 areas of child development at school entry: Physical health and well-bring (aOR=0.86, 99% CI 0.78-0.95); Language and cognitive development (aOR=0.87, 99% CI= 0.79-0.97), and Communication skills and general knowledge (aOR=0.72, 99% CI=0.64-0.80). HBCSP participation was associated with increased odds (aOR=1.19, 99% CI=1.08-1.31) of developmental vulnerability in emotional maturity. Conclusion / Implications Supported playgroup attendance in infancy is associated with positive developmental health at school entry for children with access to weekly programming. Universally accessible supported playgroups provide gap services to families in need of minimal support. Public health decision makers should consider these findings when allocating resources. These conclusions support increased access to weekly public health programming for all new parents.